Does Carbon Risk Affect The Adjustment Speed of Corporate Capital Structure? (Empirical Study on the Indonesian Stock Exchange) - Muslimin (FEB - Universitas Lampung, 2025)
This study examines how Indonesian listed companies adjust capital structure in response to carbon risk using Refinitiv Eikon data from 2015-2021. The Carbon Emissions Index is the independent variable, with Debt to Assets (DTA) and Equity to Assets (ETA) as dependent variables. A panel data model is employed, with a Fixed Effects Model for DTA and a Random Effects Model for ETA. Results indicate carbon emission risk positively moderates speed adjustment of capital structure which proxied by DTA and negatively moderates of the ETA, with adjusted R-squared values of 90.74% and 23.50%, respectively. However, carbon emission risk doesn't significantly affect overall capital structure. The DTA model better explains its influence of moderating effect of carbon emission on the speed of capital structure adjustment. Companies with higher carbon risk tend to have more debt and less equity, adjusting capital structure quickly in response to changes.